TELEMEDICINE IN RURAL AREAS: BRIDGING THE SERVICE GAP - Hariri, Ahmad; Idris, Haziq; Syarifuddin, Surya; Zahir, Roya (Yayasan Adra Karima Hubbi, 2025)
The gap in healthcare access between urban and rural areas has become a significant issue, especially in developing countries. Geographic challenges, a shortage of healthcare workers, and limited infrastructure are the main barriers for rural communities in obtaining adequate healthcare services. Telemedicine technology has emerged as a potential solution to bridge this gap by enabling remote healthcare access through digital platforms. This research aims to analyze the effectiveness of telemedicine in improving healthcare access in rural areas. The research method used is a qualitative approach with in-depth interviews and case studies in several villages that have adopted telemedicine technology. The data collected were analyzed using thematic analysis to identify key patterns related to the benefits and challenges of telemedicine implementation.The research findings indicate that telemedicine can reduce geographical barriers and enhance access to healthcare services, particularly in medical consultations and chronic condition monitoring. However, the study also reveals several challenges in its implementation, such as limited digital infrastructure, low technological literacy, and cultural resistance to new technology in some rural communities. In conclusion, telemedicine offers a promising solution to bridge the healthcare access gap in rural areas, but effective implementation requires adequate infrastructure support, community training, and supportive policies. Further research is recommended to explore ways to overcome these challenges to improve the acceptance and effectiveness of telemedicine in rural regions.